Impact of the EU Blue Card programme on cultural participation and subjective well-being of migrants in Germany. - Eleftherios Giovanis (Public Library of Science (PLoS), 2021)
The first aim of this study is to investigate the role of the EU Blue Card programme implemented in 2012 in Germany. In particular, we aim to explore the impact on the participation in cultural activities of first-generation non-European Union (EU) and non-European Economic Area (EEA) migrants, such as attendance to cinema, concerts and theatre. The second aim is to examine the impact of cultural activities on subjective well-being (SWB), measured by life satisfaction. We compare the cultural participation and life satisfaction between the treatment group that is the non-EU/EEA first-generation immigrants and the control group that consists, not only of natives and second-generation immigrants but also composes of EU/EEA first-generation immigrants who are not eligible to the programme. We will apply a sharp and a fuzzy regression discontinuity design (RDD) within a seemingly unrelated regression equations (SURE) system using the Ordered Probit method. The empirical analysis relies on data from the German Socio-Economic Panel (GSOEP) survey over the period 2015-2018. The results show that the treated subjects experience an increase in cultural participation activities and an improvement in their SWB, as a result of the EU Blue Card programme, compared to the control group. Participation in classical music performance, opera or theatre influences more the SWB compared to other cultural activities. Policies that promote labour market integration and participation in cultural activities will enable immigrants to integrate into the social norms of the host societies and improve their SWB.